An observational retrospective evaluation of 79 young men with long‐term adverse effects after use of finasteride against androgenetic alopecia. (13th January 2016) - Chiriacò, G.; Cauci, S.; Mazzon, G.; Trombetta, C.
Summary: Concern regarding adverse effects of finasteride is increasing. We aimed to determine the type and frequency of symptoms in men having long‐term sexual and non‐sexual side effects after finasteride treatment (a condition recently called post‐finasteride syndrome, PFS) against androgenetic alopecia (AGA). Subjects were recruited at the Urology Unit of the Trieste University‐Hospital, and from a dedicated website. Out of 79 participants, 34% were white Italians, mean age was 33.4 ± 7.60 years, mean duration of finasteride use was 27.3 ± 33.21 months; mean time from finasteride discontinuation was 44.1 ± 34.20 months. Symptoms were investigated by an ad hoc 100 questions' questionnaire, and by validated Arizona Sexual Experience Scale (ASEX) and Aging Male Symptom Scale (AMS) questionnaires. By ASEX questionnaire, 40.5% of participants declared getting and keeping erection very difficult, and 3.8% never achieved; reaching orgasm was declared very difficult by 16.5%, and never achieved by 2.5%. By the ad hoc questionnaire, the most frequent sexual symptoms referred were loss of penis sensitivity (87.3%), decreased ejaculatory force (82.3%), and low penile temperature (78.5%). The most frequent non‐sexual symptoms were reduced feeling of life pleasure or emotions (anhedonia) (75.9%); lack of mental concentration (72.2%), and loss of muscle tone/mass (51.9%). We contributed to inform about symptoms of PFS patients; unexpectedly loss of penis sensitivity was more frequent than severe erectile dysfunction and loss of muscle tone/mass was affecting half of the subjects. Further studies are necessary to investigate the pathophysiological and biochemical pathways leading to the post‐finasteride syndrome.